JavaScript & jQuery : interactive front-end web development - Duckett, Jon; Ruppert, Gilles; Moore, Jack, 1981- (Indianapolis, IN : John Wiley & Sons, Inc., 2014)
This book covers : 1. Basic programming concepts - assuming no prior knowledge of programming beyond an ability to create a web page using HTML & CSS ; 2. Core elements of the JavaScript language - so you can learn how to write your own scripts from scratch ; 3. jQuery - which will allow you to simplify the process of writing scripts (this is introduced half-way through the book once you have a solid understanding of JavaScript) ; 4. How to recreate techniques you will have seen on other web sites such as sliders, content filters, form validation, updating content using Ajax, and more. Each chapter: Breaks subjects down into bite-sized chunks with a new topic on each page ; Contains clear descriptions of syntax, each one demonstrated with inspiring code samples ; Uses diagrams and photography to explain complex concepts in a visual way. This book enables you to use & customize thousands of scripts, JavaScript APIs, and jQuery plugins that are freely available on the web as well as create your own scripts from scratch.
The ABC of programming -- Basic JavaScript instructions -- Functions, methods & objects -- Decisions & loops -- Document object model -- Events -- jQuery -- Ajax & JSON -- APIs -- Error handling & debugging -- Content panels -- Filtering, searching & sorting -- Form enhancement & validation.
Includes index.
Keywords: JavaScript (Computer program language).